Exploring Challenges and Weaknesses of Community-Based Health Promotion Programs in Past Three Decades in Iran: The Way Forward - Nastaran Keshavarz-Mohammadi; Farah-Sadat Bahraini; Safoora Degpasand (مجله دانشکده پزشکی اصفهان, 2014)
Background: Community-based initiatives including community-based health promotion (CBHP) programs have more than three decades of history in Iran. However, due to inadequate dissemination of the reports of such interventions, there is limited information or analysis of them accessible easily for health researchers and decision-makers at national or international level. This study, partially reported here, aimed to perform a situation analysis of community-based health promotion programs and interventions in Iran commissioned by WHO office in Tehran.